How Important Is Cultural Background for the Level of Intergenerational Mobility? - Daniel D. Schnitzlein (Economics Letters, 2012)
Based on brother correlations in permanent earnings for different groups of second generation immigrants, the findings in this paper indicate that cultural background is not a major determinant of the level of intergenerational economic mobility.
Additional information: This is the author's version of a work that was accepted for publication in Economics Letters. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Economics Letters 114(2012), 3, pp. 335-337 and is online available at http://dx.doi.org/10.1016/j.econlet.2011.11.007.
Keywords: J62; 330; Intergenerational mobility; Sibling correlations; Family background; Equality of opportunities; Einkommen; Soziale Mobilität; Migranten